Comparison of a fixed-dose combination of Celecoxib/PG201 [Layla®] versus co-administration of individual formulations in healthy participants: A randomized trial - Song, Ji Hye; Koh, Hyunsook; Moon, Hyun-Young; Jung, Jin-Gyu; Hong, Jang Hee; Sunwoo, Jung (Medicine (Baltimore), 2024)
Background: Osteoarthritis (OA) is a prevalent joint disease affecting the spine, hands, hips, knees, and feet. However, definitive drugs for OA are lacking, and current treatments are limited owing to inconvenient administration, inadequate functional improvement, and long-term side effects including gastrointestinal and cardiovascular adverse events. Therefore, in this study, we aimed to assess the pharmacokinetics and safety profiles of PK101, a fixed-dose combination (FDC) comprising PG201, a 12-herb extract used in OA treatment in traditional East Asian medicine, and celecoxib, a selective cyclooxygenase-2 inhibitor, by comparing its administration as an FDC and the corresponding individual formulations in healthy subjects. Patients and methods: A randomized, open-label, single-dose, 2 × 2 crossover design with a cohort of healthy participants. All subjects received a single FDC tablet (405.4 mg PG201 and 100 mg celecoxib) or the individual formulations, with 7-day washout period between administrations. The estimation of maximum plasma concentration and area under the plasma concentration-time curve from time zero to the time of the last quantifiable concentration of celecoxib involved determining the geometric mean ratios and 90% confidence intervals of the FDC compared to its individual formulations. Results: Forty-six participants were enrolled; however, only 44 completed the study. The geometric mean ratios (90% confidence intervals) for the area under the plasma concentration-time curve from time zero to the time of the last quantifiable concentration and maximum plasma concentration of celecoxib were 1.1124 (1.0601-1.1672) and 1.2788 (1.1708-1.3969), respectively. The time of maximum plasma concentration range was 1.0 to 4.0 hours and 1.0 to 6.0 hours (minimum-maximum) for the FDC and individual formulations, respectively. Seven adverse events occurred in 6 subjects. Conclusion: The systemic exposure and safety profiles of the individual and FDC formulations were similar, supporting their potential as an innovative and effective therapeutic approach for OA treatment. All relevant data are within the paper and its Supporting Information files.